Relationship of Human Resource Management Practices and Perception of Performance among the Employees of Selected Small and Medium Enterprises in the Kingdom of Bahrain - Fatema Mohamed Alaradi; Jayendira Sankar (International Journal of Engineering and Management Research, 2019)
The aim of this research was to find the relationship of human resource management practices and Perception of performance among employees of selected small and medium enterprises in the Kingdom of Bahrain by studying the status of human resource management practices in terms of career planning, compensation and benefits, performance appraisal, training and development, and employee relations and then study the level of Perception of performance in small and medium entrepreneurship in the Kingdom of Bahrain in terms of productivity, flexibility and quality. Employee performance plays a major part in any organization, it is important to increase the productivity of employees; the population of the research are employees of small and medium enterprises in the Kingdom of Bahrain. A simple random sampling was used. The questionnaire was distributed to employees and then the data converted to excel sheet and then analysed using statistical package for social scientists (SPSS). The result shows there is a relationship between independent variables (statues of human resource management practices on employees’ performance) and dependent variable (level of Perception of performance).